Acute Kidney Injury among Adult Patients with Diabetic Ketoacidosis in a Referral Hospital of Bangladesh (BIRDEM Medical Journal, 2017)
Background: Diabetic ketoacidosis (DKA) is a medical emergency. DKA may be complicated by acute kidney injury (AKI) and may require renal replacement therapy. Early detection and treatment including treatment of underlying cause and complication(s), if present, is important in determining outcome of DKA. This study was designed to evaluate the incidence of AKI among patients with DKA.Methods: This cross-sectional study was done in BIRDEM General Hospital, Dhaka, Bangladesh from 2008 to 2011. AKI was diagnosed by using acute kidney injury network (AKIN) criteria.Results: Total patients were 200 with slight female predominance (56%). Mean age of the study subjects was 37.6±7.5 years. Incidence of DKA was more in known diabetic patients (71%), more among rural population (53%) and low income group (76.5%). Infection (40.5%) was the commonest precipitating cause followed by non-adherence to insulin therapy (31%). Acute pancreatitis (5%), myocardial infarction (2%), stroke (1%) and surgery (1.5%) were less common causes and aetiology could not be identified in 14% cases. Fifty nine (29.5%) cases were complicated by AKI and among them three (5%) patients required haemodialysis. AKI was more in severe DKA (pH